Law enforcement against Indonesian army soldiers committing the criminal act of bigamy (Case Study of Supreme Court Decision Number 108 K/MIL/2023) - Riyadi, Slamet (Dynamics of Politics and Democracy, 2024)
Purpose: There are many cases of multiple marriage crimes committed by Indonesian Army soldiers who are subject to criminal penalties as stipulated in Article 279 paragraph (1) of the Criminal Code; however, law enforcement is not concrete and consistent. Based on SEMA 3 of 2015, soldiers committing multiple marriage crimes must be dismissed from military service, but in Supreme Court Decision Number 108 K/MIL/2023, they were acquitted. Given this background, the author examines how law enforcement and the impact of the decision are carried out using qualitative normative legal research with a phenomenological and descriptive case approach. Research/methodology: This study applies normative legal research using a phenomenological and descriptive case study approach. The theories used are the theory of criminal responsibility and deterrence theory. Results: The study finds that law enforcement against Indonesian Army soldiers committing multiple marriage crimes is handled through the Military Justice system under Law Number 31 of 1997. However, the acquittal in the Supreme Court decision reflects inconsistency in law enforcement and potentially weakens its deterrent effects. Conclusions: Law enforcement is conducted through military courts based on applicable laws; however, inconsistencies, such as acquittals, may undermine legal certainty and discipline within the military. Limitation: This study is limited to one Supreme Court decision and its implications for the military justice system. Contribution: This study contributes to the understanding of how inconsistencies in military court rulings affect legal integrity, institutional trust, and deterrence in the context of military criminal law.